The Health Stigma and Discrimination Framework: a global, crosscutting framework to inform research, intervention development, and policy on health-related stigmas - Stangl, Anne L.; Earnshaw, Valerie A.; Logie, Carmen H.; van Brakel, Wim; C. Simbayi, Leickness; Barré, Iman; Dovidio, John F. (BMC medicine, 2019)
Stigma is a well-documented barrier to health seeking behavior, engagement in care and adherence to treatment across a range of health conditions globally. In order to halt the stigmatization process and mitigate the harmful consequences of health-related stigma (i.e. stigma associated with health conditions), it is critical to have an explicit theoretical framework to guide intervention development, measurement, research, and policy. Existing stigma frameworks typically focus on one health condition in isolation and often concentrate on the psychological pathways occurring among individuals. This tendency has encouraged a siloed approach to research on health-related stigmas, focusing on individuals, impeding both comparisons across stigmatized conditions and research on innovations to reduce health-related stigma and improve health outcomes. We propose the Health Stigma and Discrimination Framework, which is a global, crosscutting framework based on theory, research, and practice, and demonstrate its application to a range of health conditions, including leprosy, epilepsy, mental health, cancer, HIV, and obesity/overweight. We also discuss how stigma related to race, gender, sexual orientation, class, and occupation intersects with health-related stigmas, and examine how the framework can be used to enhance research, programming, and policy efforts. Research and interventions inspired by a common framework will enable the field to identify similarities and differences in stigma processes across diseases and will amplify our collective ability to respond effectively and at-scale to a major driver of poor health outcomes globally.